2023
DOI: 10.1038/s43705-023-00245-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing ex vivo culture conditions to study human gut microbiome

Abstract: The inter-individual variations of gut microbiome contribute to the different responses toward drug therapy among populations, developing a reliable ex vivo culture method for mixed bacteria is the urgent need for predicting personal reaction to drug therapy. Unfortunately, very few attentions have been paid to the bias that could be introduced during the culture process for mixed bacteria. Here we systemically evaluated the factors that may affect the outcomes of cultured bacteria from human feces. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In comparison, 6C contained the carbohydrates found in the Macfarlane medium (15% starch, 15% pectin, 15% xylan, 8% arabinogalactan, 8% guar gum, and 38% inulin) [ 59 ], a nutrient-rich medium that closely mimics the gut chyme of healthy adults [ 59 ], and is commonly used in continuous intestinal in vitro models [ 60 ]. Finally, we incorporated two conditions designed to replicate the nutritional composition of media previously used for gut microbiota culturing, namely Brain Heart Infusion (BHI) medium [ 20 , 61 ] and Gut Microbiota Medium (GMM) [ 20 , 35 , 61 ]. Since we showed that the bicarbonate concentration affects the pH within the chamber, and given that BHI and GMM inherently lack bicarbonate, we formulated BHI-like and GMM-like media to improve the comparability of results without introducing confounding factors related to pH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In comparison, 6C contained the carbohydrates found in the Macfarlane medium (15% starch, 15% pectin, 15% xylan, 8% arabinogalactan, 8% guar gum, and 38% inulin) [ 59 ], a nutrient-rich medium that closely mimics the gut chyme of healthy adults [ 59 ], and is commonly used in continuous intestinal in vitro models [ 60 ]. Finally, we incorporated two conditions designed to replicate the nutritional composition of media previously used for gut microbiota culturing, namely Brain Heart Infusion (BHI) medium [ 20 , 61 ] and Gut Microbiota Medium (GMM) [ 20 , 35 , 61 ]. Since we showed that the bicarbonate concentration affects the pH within the chamber, and given that BHI and GMM inherently lack bicarbonate, we formulated BHI-like and GMM-like media to improve the comparability of results without introducing confounding factors related to pH.…”
Section: Resultsmentioning
confidence: 99%
“…S5B ). A previous study suggested that the ex vivo overgrowth of Enterobacteriaceae in the starch-containing medium, modified Gifu Anaerobic Medium, could be prevented by mixing it with the Bryant and Burkey medium [ 18 , 20 ]. The latter contains acetate, a known inhibitor of Enterobacteriaceae taxa, such as Escherichia coli [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, culturomics emphasizes the continuous refinement and enhancement of culture media and conditions to optimize species diversity through streamlined procedures [ 32 , 33 ]. One advantage of using solid media is its ability to facilitate visual identification and selection of microbiota based on their observable morphologies.…”
Section: Gut Microbial Isolation and Cultivationmentioning
confidence: 99%